Enterogenous cyst of the small bowel mesentery: a case report and review of the literature. Issue 1 (2nd January 2019) - Danys, Donatas; Martinaitytė, Raminta; Zacharic, Jolanta; Poskus, Eligijus; Zurauskas, Edvardas; Poskus, Tomas; Strupas, Kęstutis
Abstract: Introduction: Enterogenous cysts are a very rare congenital abnormality that can be found anywhere within the gastrointestinal tract, most commonly in the small intestine. The incidence is approximately one in 4500–10, 000 live births. Diagnosis can be suggested by ultrasound (US), computed tomography (CT) scans or magnetic resonance imaging (MRI) findings, although histological examination confirms the definitive diagnosis. Patients: We present a case of enterogenous cyst in an adult female who underwent a resection of the tumour. Results: After two years of observation, there is no evidence of tumour recurrence.